RESULTS FROM A NEW METHOD TO ASSESS THE OCCUPATIONAL LENS DOSE IN INTERVENTIONAL RADIOLOGY. Issue 1 (8th June 2017) - Cijan, B; Mukaj, M; Bonutti, F; Del Dò, E; Floreani, M; Kishta, D; Martin, E; Sponza, M; Saad, Al Mohannadi Salha
Abstract: Interventional radiology procedures have always been of particular concern because of the potential high dose to the workers. Special attention has recently been given to the lens dose: in 2011 the ICRP issued the recommendation 'Statement on Tissue Reactions' where a new limit of 20 mSv in a year, averaged over defined periods of 5 years, is given. Due to the impossibility of measuring the dose directly on the eye, there is not still a general consensus on a standardized methodology to assess the lens dose, which should be at the same time reliable, robust and simple to implement in practice. The procedure described here aims to assess the lens dose using the Hp(0.07) equivalent dose measured with a dosimeter worn at chest level above the lead apron, through a correlation with the total KAP per procedure and considering the type of the protection tools used during each procedure: glasses (with lateral shields), ceiling screen, both or neither of them and the frequency of their use.